Improvement of organizational and technological tools for assessing the effectiveness of construction and investment projects - Tugai, O.; Yesypenko, A.; Pylypchuk, O.; Molodko, O.; Zyakhor, D. (Ways to Improve Construction Efficiency, 2023)
The main principles and approaches to construction planning and production organization are taking into account the dependencies between the terms of project implementation and its cost. The basis of this methodology for determining the effectiveness of the implementation of construction projects is the methods and methods by which the participants of the construction and investment process determine the duration and cost of construction during tenders at various stages of organizational and technological development. The effectiveness of improving these methods essentially depends on how fully they take into account the specific features of the management-control, organizational-technological, and financial situations in which the construction will be carried out. A very wide and diverse list of factors can affect the structure and indicators of construction projects. Among them, for example, the relative remoteness of the main suppliers of resources from construction sites, the underdevelopment of the construction industry in some regions of the country, the influence of climatic factors on the productivity of labor, other powerful influence of elements of the external environment and the impact on project results in existing models and methods. As a result, we have a real duration of construction higher than the proposed one. This is especially relevant in conditions where improving the efficiency of capital investments in construction projects requires finding organizational and management tools to increase the level of economic relations in construction, strengthen contractual discipline, and increase the economic responsibility of builders and customers for the final results of construction projects. Implementation of construction projects is associated with high costs. In order to effectively use existing methods of construction planning and production organization in the established economic conditions, to have a positive impact on the acceleration and efficiency of construction, it is necessary to add methods that take into account the existing specific features of the construction industry. The need to create a certain toolkit for solving tasks related to increasing the efficiency of construction projects, minimizing the duration of projects and maximizing profit, taking into account organizational, technological, economic factors and elements of the external environment, determines the relevance of this scientific research.